2017
DOI: 10.1111/jdi.12594
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the anti‐glutamic acid decarboxylase antibody in type 1 diabetes mellitus: Comparison between radioimmunoassay and enzyme‐linked immunosorbent assay

Abstract: Aims/IntroductionThe distributer of the anti‐glutamic acid decarboxylase antibody assay kit using radioimmunoassay (RIA) recently announced its discontinuation, and proposed an alternative kit using enzyme‐linked immunosorbent assay (ELISA). The aim of the present study was to investigate the diagnostic values of the anti‐glutamic acid decarboxylase antibody by RIA and ELISA among type 1 diabetes mellitus patients and control participants.Materials and MethodsA total of 79 type 1 diabetes mellitus patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
(15 reference statements)
4
15
1
Order By: Relevance
“…Meanwhile, a total of 162 participants (27.1%) showed positive results in the GADA‐RIA (1.5–31.1 U/mL) and negative in the GADA‐ELISA test (<5.0 U/mL) (open circles in Figure ), which accounted for 34.0% of the GADA‐RIA‐positive participants ( n = 477). This considerable mismatch rate is higher than those previously reported (17.4–25.5%). Similar to previous reports, the mismatch was mainly observed in participants with relatively low GADA‐RIA levels (1.5–32 U/mL).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Meanwhile, a total of 162 participants (27.1%) showed positive results in the GADA‐RIA (1.5–31.1 U/mL) and negative in the GADA‐ELISA test (<5.0 U/mL) (open circles in Figure ), which accounted for 34.0% of the GADA‐RIA‐positive participants ( n = 477). This considerable mismatch rate is higher than those previously reported (17.4–25.5%). Similar to previous reports, the mismatch was mainly observed in participants with relatively low GADA‐RIA levels (1.5–32 U/mL).…”
Section: Resultssupporting
confidence: 85%
“…This considerable mismatch rate is higher than those previously reported (17.4–25.5%). Similar to previous reports, the mismatch was mainly observed in participants with relatively low GADA‐RIA levels (1.5–32 U/mL). When considering lower GADA‐RIA levels alone (1.5–32 U/mL), GADA‐ELISA‐negative participants accounted for 44.8% (162/362) of the GADA‐RIA‐positive participants.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…An example of this is in cases of a single subtype of type 1 diabetes that might not be included in these results, as those patients whose GADA turned positive by modified ELISA protocol consisted of all three subtypes of type 1 diabetes; that is, acute‐onset, fulminant and slowly progressive type 1 diabetes. It has been reported that the GADA titer in RIA(+)/ELISA(−) sera is lower than in RIA(+)/ELISA(+) sera. In general, high‐affinity antibodies bind a greater amount of antigen in a shorter period of time than low‐affinity antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, measurement of GADA has changed from RIA to non‐radioactive enzyme‐linked immunosorbent assay (GADA‐ELISA) in Japan. This commercially available GADA‐ELISA is reported to have higher specificity for the diagnosis of type 1 diabetes, as compared with GADA‐RIA. However, the correlation between GADA titers, as measured with GADA‐ELISA, and residual β‐cell function has not been fully investigated in patients with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%